2010
DOI: 10.1007/s11240-010-9773-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis induction in leaves and petioles of a mature wild olive

Abstract: We describe a protocol for somatic embryogenesis (SE) induction from an adult wild olive tree (Olea europaea ssp. europaea var. sylvestris. The protocol used confirms for the first time that there is no need to use juvenile or rejuvenated material for SE induction. For SE induction, petiole and leaf (proximal, intermediary and distal zones) explants were grown on Murashige and Skoog (MS) or Olive Medium (OM) media with different combinations of plant growth regulators (PGR): a-naphthaleneacetic acid (NAA), Zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…However, 4-CPA has been successfully used in other species such as Pisum sativum (Loiseau et al 1995), Rosa sp. Auxins are involved in regulating the cell cycle and promoting cell differentiation and play important roles in somatic embryogenesis in several species (Jiménez 2005, Kurczynska et al 2007, Capelo et al 2011, Rocha et al 2012). …”
Section: Induction Of Somatic Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, 4-CPA has been successfully used in other species such as Pisum sativum (Loiseau et al 1995), Rosa sp. Auxins are involved in regulating the cell cycle and promoting cell differentiation and play important roles in somatic embryogenesis in several species (Jiménez 2005, Kurczynska et al 2007, Capelo et al 2011, Rocha et al 2012). …”
Section: Induction Of Somatic Embryogenesismentioning
confidence: 99%
“…The genotype may influence the variation of embryogenic responses during the induction and maturation phase in plant tissue (Bell et al 1993). In addition, factors such as the type and concentration of auxin (Anandan et al 2012), the type of explant (Capelo et al 2011), presence or absence of abscisic acid (Bell et al 1993), activated carbon (López-Pérez et al 2005) or osmotic substances (Heringer et al 2013) can alter the responses among genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Auxins and cytokinin are the main plant growth regulators involved in the regulation of plant cell cycling, division and differentiation, playing key roles in somatic embryogenesis of many species (Fehér et al 2003;Jiménez 2005;Capelo et al 2011;Cerezo et al 2011;Parimalan et al 2011;Paul et al 2011;You et al 2011).…”
Section: Embryogenic Callus Inductionmentioning
confidence: 99%
“…Furthermore, SE has become a widely used technique in genetic transformation and mass propagation of elite genotypes (Table 1). Light and electron microscopic studies have reported on the cellular origin of somatic embryos during primary (Blazquez et al 2009;Capelo et al 2010;Lin et al 2011;Parra-Vega et al 2013) and repetitive/secondary embryogenesis (Dai et al 2011;Pavlović et al 2013;Raju et al 2013). Upon exposure to SE induction medium, the initial events signifying cytological changes in the formation of somatic embryos were evident in 4-6 days (Canhoto et al 1996;Kurczyńska et al 2007).…”
Section: Somatic Embryogenesismentioning
confidence: 99%